A LONGITUDINAL STUDY OF THE COMPETITIVE POSITIONS AND ENTRY PATHS OF EUROPEAN FIRMS IN THE U.S. PHARMACEUTICAL MARKET - Bogner, William C.; Thomas, Howard; McGee, John (Strategic Management Journal, 1996)
This paper combines the statistical insights of dynamic strategic group analysis with the qualitative richness of historical analysis to explore the modes of entry, expansion paths, and competitive postures of European firms in the U.S. pharmaceutical market. Patterns of entry and market development over a 20-year period are analyzed. The roles of strategic assets and competencies in determining both the entry strategy and the final competitive posture of these firms in the U.S. market are discussed.